1998
DOI: 10.1034/j.1600-0420.1998.760423.x
|View full text |Cite
|
Sign up to set email alerts
|

Juvenile nasopharyngeal angiofibroma ‐ A rare case of primary orbital development

Abstract: ABSTRACT.Purpose: To present a rare case of juvenile nasopharyngeal angiofibroma invading the ophthalmic orbit. Methods: The CT scan examination and the ultrasound tomography revealed the existence of a homogenous solid mass causing distention and erosion of the nasal wall as well as dislocation of the ocular bulbus. Result: The patient was operated, the mass was carefully liberated from its synechiae and it was totally excised with its capsule. Conclusion: A rare case of juvenile nasopharyngeal angiofibroma i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…The blood supply is derived from the sphenopalatine artery [218]. Occasionally the mass extends into the sinus [219], and rare extranasopharyngeal cases have been reported in the ethmoid and maxillary sinuses [220][221][222][223][224][225]. Nasopharyngeal angiofibroma is 25 times more frequent in patients with familial adenomatous polyposis and may be associated with APC and beta-catenin mutations [226][227][228][229][230][231][232][233][234].…”
Section: Juvenile Nasopharyngeal Fibroma (Angiofibroma)mentioning
confidence: 99%
“…The blood supply is derived from the sphenopalatine artery [218]. Occasionally the mass extends into the sinus [219], and rare extranasopharyngeal cases have been reported in the ethmoid and maxillary sinuses [220][221][222][223][224][225]. Nasopharyngeal angiofibroma is 25 times more frequent in patients with familial adenomatous polyposis and may be associated with APC and beta-catenin mutations [226][227][228][229][230][231][232][233][234].…”
Section: Juvenile Nasopharyngeal Fibroma (Angiofibroma)mentioning
confidence: 99%
“…The first such reported case presented with advanced proptosis, diplopia, epiphora, and no nasal symptoms. 4 Ganesh and colleagues 5 described a patient who presented with orbital apex syndrome. They suggested that a high level of suspicion be maintained while treating an adolescent male with chronic nasal obstruction, epistaxis, and a nasal mass.…”
Section: Discussionmentioning
confidence: 98%
“…Other sites of origin have been described, including the pterygopalatine fossa, the nasopharynx at the base of the sphenoid bone, the sphenoid sinus, paranasal region, and the lacrimal sac [5][6][7]. The tumor grows in the submucosal plane, spreading medially into the nasal cavity and nasopharynx [8,9].…”
Section: Origin and Spread Of Jnamentioning
confidence: 99%